Brain-Targeted Delivery of Pre-miR-29b Using Lactoferrin-Stearic Acid-Modified-Chitosan/Polyethyleneimine Polyplexes - Pereira, Patrícia (2020)
The efficacy of brain therapeutics is largely hampered by the presence of the blood-brain barrier (BBB), mainly due to the failure of most (bio) pharmaceuticals to cross it. Accordingly, this study aims to develop nanocarriers for targeted delivery of recombinant precursor microRNA (pre-miR-29b), foreseeing a decrease in the expression of the BACE1 protein, with potential implications in Alzheimer's disease (AD) treatment. Stearic acid (SA) and lactoferrin (Lf) were successfully exploited as brain-targeting ligands to modify cationic polymers (chitosan (CS) or polyethyleneimine (PEI)), and its BBB penetration behavior was evaluated. The intracellular uptake of the dual-targeting drug delivery systems by neuronal cell models, as well as the gene silencing efficiency of recombinant pre-miR-29b, was analyzed in vitro. Labeled pre-miR-29b-CS/PEI-SA-Lf systems showed very strong fluorescence in the cytoplasm and nucleus of RBE4 cells, being verified the delivery of pre-miR-29b to neuronal cells after 1 h transfection. The experiment of transport across the BBB showed that CS-SA-Lf delivered 65% of recombinant pre-miR-29b in a period of 4 h, a significantly higher transport ratio than the 42% found for PEI-SA-Lf in the same time frame. Overall, a novel procedure for the dual targeting of DDS is disclosed, opening new perspectives in nanomedicines delivery, whereby a novel drug delivery system harvests the merits and properties of the different immobilized ligands.